2013
DOI: 10.1155/2013/871689
|View full text |Cite
|
Sign up to set email alerts
|

Role of Color Doppler Imaging in Early Diagnosis and Prediction of Progression in Glaucoma

Abstract: This longitudinal and prospective study analyzes the ability of orbital blood flow measured by color Doppler imaging (CDI) to predict glaucoma progression in patients with glaucoma risk factors. Patients with normal perimetry but having glaucoma risk factors and patients in the initial phase of glaucoma were prospectively included in the study and divided, after a five-year follow-up, into two groups: “Progression” and “No Progression” based on the changes in the Moorfields regression analysis (MRA) classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
1
19
2
1
Order By: Relevance
“…These findings are similar to those in studies of POAG eyes where the peripapillary microcirculation was highly correlated with VF pattern standard. 18,2729 In contrast with the PACG eyes in our study, there were no correlations between peripapillary retinal VD and other glaucoma parameters in the unaffected eyes. This indicated that loss of peripapillary retinal VD is associated with acute PACG.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings are similar to those in studies of POAG eyes where the peripapillary microcirculation was highly correlated with VF pattern standard. 18,2729 In contrast with the PACG eyes in our study, there were no correlations between peripapillary retinal VD and other glaucoma parameters in the unaffected eyes. This indicated that loss of peripapillary retinal VD is associated with acute PACG.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings are supported by previous studies where Calvo et al reported that OA EDV and mean velocity were reduced in subjects who converted to glaucoma based on Moorfields Regression Analysis 22. Jimenez-Aragon et al found that the EDV and RI of the OA and CRA were significantly different between subjects who structurally progressed compared with those who did not progress 23. Additionally, Calvo et al reported that an OA RI value higher than 0.75 was associated with the development of glaucoma 22.…”
Section: Discussionsupporting
confidence: 84%
“…found that the EDV and RI of the OA and CRA were significantly different between subjects who structurally progressed compared to those who did not progress. 55 Zeitz et al . showed that the EDV and PSV of the short posterior ciliary arteries were decreased in subjects who structurally progressed.…”
Section: Discussionmentioning
confidence: 99%